Correlation between aboveground vegetation composition and soil seed bank of Raudhat desert habitat: a case study of Raudhat Alkhafs, Saudi Arabia - Asma A. Al-Huqail; Hanan F. Al-Harbi; Abdullah M. Alowaifeer; Mohamed A. El-Sheikh; Abdulaziz M. Assaeed; Turki S. Alsaleem; Hazem S. Kassem; Omar M. Azab; Basharat A. Dar; Jahangir A. Malik; Ahmed M. Abd-ElGawad (BMC Plant Biology)
Abstract Plant diversity in arid environments is very important for ecosystem function and services. Raudhat habitat is among the most important ecosystems in the arid regions which is characterized by its rich biodiversity and specific environmental conditions. The present study aims to characterize plant communities and soil seed banks of the Raudhat Alkhafs, northeast of Riyadh City, Saudi Arabia. Vegetation composition was analyzed during the winter-spring and summer-fall seasons. Soil samples were collected from each site for seed bank analysis through seedling emergence techniques and for chemical and physical analyses. Eighty-three plant species were recorded (50.6% perennial and 49.4% annual plants). Among 30 plant families, Asteraceae, Poaceae, Brassicaceae, Boraginaceae, and Fabaceae were frequent (50.6%). Therophytes are distinguished as major (45.8%) because of their ability to tolerate arid environments, high reproduction rate, ecological flexibility, and genetic plasticity. Vegetation analysis showed three plant communities in the winter-spring season dominated by Plantago ciliata, Calotropis procera, and Heliotropium ramosissimum, while in the summer-fall season, Calotropis procera dominated one community, while two other plant communities were dominated by Heliotropium ramosissimum. During the winter-spring season, Heliotropium ramosissimum community revealed the highest species richness (Simpson index = 0.92) and evenness (Shannon-evenness = 0.83). These variations among the two seasons in the species composition can be ascribed to the climatic conditions. For plant communities identified during the winter-spring season, the soil analysis revealed significant variations in salinity, soil texture, water holding capacity, H2CO3, K, and Na contents. However, the communities identified in the summer-fall season showed significant variations in salinity, soil texture, and Cl, and Mg contents. Regarding the soil seed bank, 22 plant species were identified in the soil samples, mainly annuals. The density of the seed bank ranged from 156 to 1339 seeds/m2. Trigonella stellata Forssk. attained the highest number of seeds in the soil (1628 seeds/m2), followed by Plantago ciliata (1000 seeds/m2) and Poa annua (889 seeds/m2). About 45% of the plant species recorded in the present study were not identified in the soil seed bank earlier in Raudhat Alkhafs. The low correlation between the aboveground vegetation and the soil seed bank of the northern part of the studied region revealed the degradation of the habitat which could be due to overgrazing and anthropogenic activities. Based on the obtained results, the sites of AlKhafs-North need immediate restoration and rehabilitation to conserve this very important biodiversity site.